Novel Insight Into the Role of ACSL1 Gene in Milk Production Traits in Buffalo - Lin, Yuxin; Sun, Hui; Shaukat, Aftab; Deng, Tingxian; Abdel-Shafy, Hamdy; Che, Zhaoxuan; Zhou, Yang; Hu, Changmin; Li, Huazhao; Wu, Qipeng; Yang, Liguo; Hua, Guohua (Frontiers in Genetics, 2022)
Understanding genetic mechanisms underlying milk production traits can assist to improve the production potential of dairy animals. Long-chain acyl-CoA synthetase 1 (ACSL1) plays a key role in fatty acids metabolism, and was highly expressed in the lactating mammary gland epithelial cells (MGECs), which indicated its critical role on lactation regulation. The objectives of the present study were to detect the polymorphisms within ACSL1 gene in Mediterinian buffalo, to investigate the genetic effects of these mutations on milk production traits, and to understand the gene regulatory effects on MGECs. A total of twelve SNPs were identified by sequencing, including nine SNPs in intronic region and three in the exonic region. Association analysis between these twelve SNP genotypes and milk production traits showed that nine SNPs were associated with one or more trait. We inferred two haplotype blocks from phased genotypes of the twelve SNPs. Among these haplotypes, the individuals carrying H2H2 haplotype in block1 and H5H1 in block2 were superior to other haplotypes in milk production traits. Immunohistological staining of ACSL1 in buffalo mammary gland tissue indicated its expression and localization in MGECs. The regulatory effects of ACSL1 were then comfirmed in MGECs. Knockdown of ACSL1 inhibited cell growth, diminished MGECs lipid systhesis and triglyceride secretion, and downregulated CCND1, PPARγ, and FABP3 expression. Overexpression of ACSL1 promoted cell growth, enhanced the tryglyceride secretion, and upregulated CCND1, PPARγ, SREBP1, and FABP3. ACSL1 also involved in milk protein regulation as indicated by the dereased or increased β-casein concentration and CSN3 expression in knowdown or overexpression group, respectively. In summary, our present study depicted that the identified SNPs in ACSL1 were associated with buffalo milk production performance. This maybe related with its positive regulation roles on MGECs growth, milk fat and milk protein systhesis. Our result showed the potential of ACSL1 gene as candidate for milk production traits, and provide new understanding on the physiological mechanisms underlying milk production regulation.